A evolução metafísica da teoria do delito - Aguirre, Eduardo Küpper Pacheco de (2010)
This work analyzed the metaphysic evolution of the Theory of Crime causal theory by starting and finishing in the finalist theory. The concept of crime over several times has been undergoing changes and to describe them were found the philosophical underpinnings of each of these currents. Were evaluated with different dogmatic approaches of scholars such as Liszt, Beling, among others. We conclude believing that discussions on the concept of crime should not end quite the contrary, the existence of climate and new understandings of criminal acts must always be present in the intricacies of criminal law in order that the theory can continue evolving and largely given to the interests of society